Evidence that autosomal recessive spastic cerebral palsy-1 (CPSQ1) is caused by a missense variant in HPDL. Issue 1 (28th January 2021) - Morgan, Neil V; Yngvadottir, Bryndis; O'Driscoll, Mary; Clark, Graeme R; Walsh, Diana; Martin, Ezequiel; Tee, Louise; Reid, Evan; Titheradge, Hannah L; Maher, Eamonn R
Abstract: A subset of individuals diagnosed with cerebral palsy will have an underlying genetic diagnosis. Previously, a missense variant in GAD1 was described as a candidate mutation in a single family diagnosed with autosomal recessive spastic cerebral palsy-1 (CPSQ1; OMIM 603513). Following the ascertainment of a further branch of the CPSQ1 kindred, we found that the previously reported GAD1 variant did not segregate with the neurological disease phenotype in the recently ascertained branch of the kindred. Following genetic linkage studies to map autozygous regions and whole-exome sequencing, a missense variant (c.527 T > C; p. Leu176Pro, rs773333490) in the HPDL gene was detected and found to segregate with disease status in both branches of the kindred. HPDL encodes a 371-amino acid protein (4-Hydroxyphenylpyruvate Dioxygenase Like) that localizes to mitochondria but whose function is uncertain. Recently, biallelic loss of function variants and missense substitution-causing variants in HPDL were reported to cause a childhood onset progressive spastic movement disorder with a variable presentation. These findings suggest that HPDL- related neurological disease may mimic spastic cerebral palsy and that GAD1 should not be included in diagnostic gene panels for inherited cerebral palsy. Abstract : Morgan et al. report that a novel candidate mutation in the HPDL gene (but not GAD1 ) segregates with disease status within a kindred in which a locus for autosomal recessive spastic cerebral palsy-1 (CPSQ1; OMIM 603513, GAD1 ) was mapped previously (in part of the kindred). Graphical Abstract: